Modification of Diffie–Hellman Key Exchange Algorithm for Zero Knowledge Proof - Mahmood Khalel Ibrahim (Engineering and Technology Journal, 2012)
Networks and entity groupings requires entity authentication while preserving the privacy of the entity being authenticated. Zero-Knowledge Proof (ZKP) plays an important role in authentication without revealing secret information. Diffie–Hellman (D-H) key exchange algorithm was developed to exchange secret keys through unprotected channels. This paper discusses zero-knowledge protocols and Diffie– Hellman algorithm and analyzes their vulnerability against known attacks. Also it presents a proposed protocol based on modification of Diffie–Hellman algorithm into an interactive zero-knowledge proof protocol. The proposed protocol is designed and developed to satisfy the zero-knowledge proof properties and resists the known attacks